Evaluation of urban resilience level and analysis of obstacle factors: A case study of Hunan Province, China - Chen, Na; Guo, Hongxia; Xiang, Hui (Frontiers in Earth Science, 2023)
Resilient city is an ideal goal and model of urban development proposed in response to today’s complex and dynamic environmental changes. In this study, a resilient city evaluation framework composed of “social resilience-economic resilience-urban infrastructure and service-urban governance” was built on the basis of the multi-dimensionality of the urban system; the entropy weight method was used to measure the level of urban resilience in Hunan Province, while an obstacle degree model was used to identify any obstacle factor restricting the development of resilience. The results show that the urban resilience level of Hunan Province has grown slowly over the past 10 years, and there is an obvious regional difference in urban resilience level. There are more and more highly resilient cities, but low and medium-resilience cities still dominate the province, forming a spatial process of evolution from “medium and high-level dispersion” to “medium and high-level aggregation” in the Changsha-Zhuzhou-Xiangtan Urban Agglomeration. The level of urban resilience is predominantly hindered by the social and economic systems; at the index layer, most obstacle factors exist from the economic system to the social-economic-urban infrastructure and service system.